THE EXERCISE OF SYMBOLIC VIOLENCE IN HEALTH CARE OF MIDDLE-AGE WOMEN EXPERIENCING MENOPAUSE: KEY RESULTS OF A KAP SURVEY - Castillo Vargas, Andrés (2013)
This article analyzes the symbolic violence to the light of knowledge, attitudes and practices that health staff have about the care of middle-aged women experiencing menopause. At the methodological level, it was proposed an exploratory-descriptive study. The method used was KAP survey (Knowledge, Attitudes and Practices). This approach identified as an important finding, the need to promote a paradigm shift regarding the traditional view of menstrual cessation and how your approach has been devised.